The Ritual Calendar of South Aceh, Indonesia - Manan, Abdul (Jurnal Ilmiah Peuradeun, 2017)
This research explores the relations between the so-called normative Islam-as laid down in the canonical texts of the Qurâ€™Än and hadÄ«th-and the ways in which these normative ideas, perceptions and values are expressed in rituals in the society concerned. It pays particular attention to the ways in which the latter forms of ritual expression entail a culturally specific adaptation and valorization of the trans-cultural representations laid down in these Islamic text corpora and to the ways in which-according to local understanding and exegesis-these ritual actions generate a reproduction of the social relationships and their moral foundation in the society concerned. In-depth discussions had been conducted with the participants about the symbols, meanings and values, which they attach to these actions as to their effectiveness in achieving particular social, religious, political and moral aims besides a systematic survey of relevant published sources has complemented this field research. The meticulous examination of the village ritual calendar shows that three different perspectives on this social and moral order prevail: a traditional adat perspective, the historical Islamic perspective, and the modernist Islamic perspective. This attributes to Aneuk Jamee a complex dynamic socio-religious identity within the field of Indonesian cultures.